2013
DOI: 10.1007/s00232-013-9566-3
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Hawthorn Leaf and Bark Extracts in Relation to Biological Membrane

Abstract: The aim of the study was to identify and determine the percent content of polyphenols in extracts from leaves and hawthorn bark, to examine the effect of the extracts on the properties of the biological membrane as well as to determine their antioxidant activity toward membrane lipids. In particular, a biophysical investigation was conducted on the effect of hawthorn extracts on the osmotic resistance and morphology of erythrocyte cells and on the packing of the heads of membrane lipids. Analysis of the polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Oszmiański and Bourzeix detected 450 mg of procyanidin per 100 g fresh bark . Włoch et al reported 561.59 mg g −1 DW in the bark extract . According to Wu et al , the content of procyanidins in the skin, pulp and seed of monogyna hawthorn were 2.93 mg g −1 FW, 0.65 mg g −1 FW and 3.25 mg g −1 FW, respectively .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Oszmiański and Bourzeix detected 450 mg of procyanidin per 100 g fresh bark . Włoch et al reported 561.59 mg g −1 DW in the bark extract . According to Wu et al , the content of procyanidins in the skin, pulp and seed of monogyna hawthorn were 2.93 mg g −1 FW, 0.65 mg g −1 FW and 3.25 mg g −1 FW, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…The antioxidant activity as well as the procyanidin content was significantly higher in the extract from hawthorn bark [1069 µmol L −1 TE g −1 (DPPH); 6110 µmol L −1 TE g −1 (ABTS); 2639 µmol L −1 TE g −1 (FRAP)) than in methanolic extract of fruits (195 µmol L −1 TE g −1 (DPPH); 218 µmol L −1 TE g −1 (ABTS); 232 µmol L −1 TE g −1 (FRAP)]. Włoch et al measured two times higher activity in bark extract (12 900 µmol L −1 TE g −1 DW) against ABTS radical, than in this study . In the hawthorn bark they identified additional compounds, from the group of flavonols, phenolic acids and vitexin derivatives, which could have an impact on higher antioxidant activity of the extract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method determines the location of compounds in the membrane based on the shape of blood cells, described earlier by Włoch et al (2013). The optical instrument (Nikon Eclipse E200) equipped with a digital camera and scanning electron microscope (EVO LS15 ZEISS) were used in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, alteration of lipid bilayer properties may result not only in antioxidant action of flavonoids but also in affecting the activity of integral proteins and hence influence transport and other membrane-related processes [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The ability of polyphenols to penetrate into lipid bilayers is undoubtedly crucial to the protection against oxidation [42].…”
Section: Introductionmentioning
confidence: 99%